Association between trigeminal neuralgia and multiple sclerosis: role of magnetic resonance imaging. Issue 3 (September 1995) - Meaney, J F; Watt, J W; Eldridge, P R; Whitehouse, G H; Wells, J C; Miles, J B
Abstract : Seven consecutive patients with multiple sclerosis and trigeminal neuralgia were investigated with MRI to determine the occurrence of a lesion which would account for the patients' pain. Two patients had bilateral symptoms. In the patients with unilateral trigeminal neuralgia vascular compression of the nerve by an artery at the root entry zone on the symptomatic side was confirmed in three patients and an epidermoid tumour distorting the nerve on the symptomatic side was identified in one patient. A demyelinating plaque was identified in only one patient, affecting the trigeminal nerve at the root entry zone at the pons. In those with bilateral symptoms neurovascular compression was identified on both sides in one patient and on one side only in the remaining patient. Microvascular decompression cured the pain in two patients with neurovascular compression. The variable aetiology of trigeminal neuralgia is stressed even in patients with coexistent neurological conditions such as multiple sclerosis, which can cause trigeminal neuralgia independent of other causes.